Elevated Serum Leptin Levels as a Predictive Marker for Polycystic Ovary Syndrome - Peng, Yuanyuan; Yang, Hongyue; Song, Jiahui; Feng, Di; Na, Zhijing; Jiang, Hongyu; Meng, Yaxin; Shi, Bei; Li, Da (Frontiers in Endocrinology, 2022)
Background: Leptin may have important implications in polycystic ovary syndrome (PCOS)-related metabolic disorders. However, the changes in serum leptin levels in patients with PCOS and its predictive value for PCOS remain obscure. We intend to analyze the association between leptin and PCOS in this study. Materials and Methods: The study comprised 89 patients with PCOS and 139 individuals without PCOS. Each group was stratified as either normal- or hyper-fasting serum insulin (FSI), and lean or overweight/obese; and the patients were further categorized as normal- or hyper-androgenic. The validity of leptin toward the diagnosis of PCOS, or leptin combined with total testosterone, dehydroepiandrosterone sulfate (DHEAS), and free testosterone was estimated by receiver operating characteristic (ROC) curves, and correlations between paired variables was estimated by Spearman's rank correlation coefficient. Associations between the clinical and metabolic variables and PCOS were analyzed via logistic regression. Results: The serum leptin levels of patients with PCOS were significantly higher than that of the control, and especially the PCOS in hyper-FSI, hyperandrogenimic and overweight/obese subgroups. The area under the ROC curve (AUC) of leptin was 74%, with cutoff value, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) 11.58 ng/mL, 77.5%, 62.6%, 57.0%, and 81.3%, respectively. Combined leptin and anti-Müllerian hormone (AMH) had the highest AUC (92.3%), excellent sensitivity (93.3%), moderate specificity (78.3%), PPV (73.5%) and NPV (94.8%). Serum leptin levels of the patients were correlated with the FSI, fasting plasma glucose (FPG), homeostasis model assessment of insulin resistance (HOMA-IR), body mass index (BMI), and total testosterone levels. Elevated serum leptin was associated with a high risk of PCOS (P = 0.015; OR [95% CI] 1.128 [1.024–1.244]). Conclusion: Substantially elevated serum leptin is significantly associated with PCOS. These findings warrant further investigations into the function of leptin in the pathogenesis of PCOS.